Alimento extrusado à base de farelo de mamona na dieta de cabras lactantes - Santos, Sueli Freitas dos (2012)
This study was conducted to evaluate the performance and quality of dairy goats fed milk diets containing extruded food-based castor meal (EFCM) in dairy goats. Four groups of five female Saanen goats, were fed with diets with different levels of soybean meal replacement by ECCM: 0, 33, 67 and 100%, for 34 days. There was no treatment effect (P>0.05) on the evaluated nutrients intake: dry matter (g/d, %BW and g/kg BW0.75), crude protein (g/d and g/kg BW0.75), extract ether (g/d and g/kg BW0.75), neutral detergent fiber (g/d, %BW and g/kg BW0.75), non-fibrous carbohydrates (g/kg BW0.75) and total carbohydrates (g/d and g/kg BW0.75). The non-fibrous carbohydrate intake (g / d) was affected (P <0.05), presenting a positive linear relashionship with inclusion level of EFCM. Was no influence of treatment on the DMD, OMD, CPD, NDFD DEE and nutrients, causing linear effect (P <0.05). As well as in DCNF that showed a quadratic effect (P <0.05). There was no influence of the treatments (P> 0.05) on the consumed nitrogen parameters, nitrogen excreted in the urine nitrogen excreted in milk, nitrogen balance, the total nitrogen excretion and basal endogenous nitrogen. It was observed that the values found for fecal nitrogen, were affected (P <0.05). The parameters of the physical and chemical composition of milk, it was observed that there was no effect (P> 0.05) on milk production (PM), in gross composition of milk protein (PMC) and milk fat (MF).The average values of milk urea nitrogen (MUN) were affected (P <0.05) compared with control diet. There was no effect (P> 0.05) on lactose (LAC), and total solids (TS).For dry extract variables defatted and yield of cheese, there was influence (P<0.05), averaging 76,42g.kg-1 and 22.25%. The concentration of the butyric acid content in fatty acids (C4: 0) and caprylic (C8: 0) were affected (P <0.05) when compared to the control treatment. There was no effect (P> 0.05) on the levels of saturated fatty acids (SFA), unsaturated fatty acid (UFA), polyunsaturated fatty acids (PUFA). For the atherogenicity index (IA) showed a significant effect (P <0.05), demonstrating best results in 33% replacement level. The variables characteristic odor, strange odor, characteristic taste, strange taste, rancid flavor, sweet taste and overall acceptability were affected (P<0.05), with averages of 3.24, 2.88, 5.20, 3, 86, 3.49, 4.10 and 4.36% respectively. The results indicate that the EFCM, despite causing a reduction in the digestibility of nutrients, can be used in replacement of soybean meal in diets of dairy goats without reductions in nutrient intake without affecting the production and quality of milk, and without providing any damage to animal health.